Textile Composite Materials A review - M.EI Arab, Salah (Gezira Journal of Engineering and Applied Sciences, 2013)
Textiles  have a lot to do in the manufacturing of composite materials. The challenge  is -how to -make a textile  preform  that suits a special composite   material   manufacture   for   a specific   requirement   of applications   which   is  composed  of   too   many   areas. The   high performance  materials  like  glass. Carbon  and  aramid fibres can be used  in  textile composites  manufacturing  being  made in  different structures and preforms to give the most popular properties. They can be  used  separately  or  in  a combination  to provide the optimum or even  the  most  acceptable balance of properties dealing with strength and   stiffness  through   the   fibre   axis   or   in   different  directions according  to  their  end – use. The  matrices  should  also be selected carefully to  suit  the requirement of the end-use of the composite and their  life time  should  be put  into account. Since composites can be made  to  suit  any  application  by  tailoring  their   properties, textile preforms  with  different structures can be produced as a raw material, with the most popular properties being guaranteed in the first steps of design of the preform. Natural fibres can also be to used to make composite materials making benefit from their different properties, with specified matrix materials of synthetic or  natural origin.